Development of Supplementary Book of Writing Skills for Beginner with Local Wisdom Content for Elementary School Students (Journal of Primary Education, 2019)
The objectives of this study are to analyze the need to develop supplementary book of writing skills for beginner with local wisdom content for second grade elementary school students, develop an supplementary book products, and test the effectiveness of supplementary book products. This research used a research and development method with seven steps, they are a preliminary study, analysis of development needs, initial product development, product validation and product revision, small-scale trials and product revisions, wide-scale trials and product improvement, final products. Research data were collected through a needs questionnaire, validation sheets, pre-test and post-test questions, and response questionnaires. The results of the research show that supplementary writing books are needed in the process of learning of writing for beginner. The results of the validation of the supplementary book are 74.69% with a valid category and the learning outcomes of the aspects of knowledge and skills improve with the score of n-gain 0.63 in the aspects of knowledge and 0.57 in the aspects of skills. Based on the results of the validation and effectiveness test the effective supplementary book is used as a complement book in the learning process.